Sustainable financial integration and community economic resilience in financial planning: A phenomenological study in the Semeru Huntap community market - Nuha, Sukma Uli; Nazlia, Nurul; Nuha, Ria Meilan (Journal of Multiperspectives on Accounting Literature, 2026)
Purpose: This research aims to understand how sustainable finance principles are implemented and how these practices affect the economic resilience of communities in the Semeru Huntap Community Market. Methodology/approach: Qualitative research with a phenomenological approach. The informants for this research were business owners at the Semeru Huntap Community Market. Data analysis techniques included data reduction, data presentation, verification, and conclusion drawing. Data validity was tested using the triangulation method. Findings: Research on the integration of sustainable finance in the context of post-disaster communities has a unique character, namely that fragile economic conditions urge the development of an adaptive and resilient financial system, so that this research contributes to the development of community-based economic recovery policies. Practical implications: This research is expected to be a basis for designing empowerment programs, capital, financial literacy training and economic support policies that are more targeted to disaster survivor communities. Originality/value: This research has a unique character, namely by understanding real experiences, it provides a comprehensive picture of the principles of sustainable finance integrated both consciously and unconsciously in the activities of business actors in the Semeru Huntap Community Market.